Strategi Manajemen Pendidikan Islam di Era Society 5.0: Integrasi Nilai Spiritual dan Inovasi Digital - Saputra, Yusril Ihza; Rohman, Muhammad Kholilur; Kamil, Moh.; Abrar, Muhammad Thoiful; Holidi, Moh.; Muhlas, Moh.; Mudarris, Badrul (CV. Lentera Literasi Indonesia, 2025)
This study aims to analyze Islamic education management strategies in the Society 5.0 era, focusing on the integration of spiritual values ​​and digital innovation at MA Al-Ma'arif NU Pujer, Bondowoso. The research approach used a qualitative method with a case study design. Data were collected through observation, in-depth interviews with the madrasah principal and teachers, and a review of school documents. Data analysis was conducted through the stages of data condensation, data presentation, and verification using interpretive analysis techniques. The results indicate that transformational and collaborative leadership are the main factors driving Islamic digital innovation in madrasahs. The madrasah principal acts as an inspirational figure who instills spiritual values ​​in every digitalization policy, creating synergy between technological advancements and the development of students' religious character. Furthermore, collaborative strategies between teachers and educational staff strengthen an ethical and productive digital culture. The implications of this study indicate that spirituality-based Islamic education management can adapt to the demands of the digital era without losing its Islamic identity. These findings can serve as a model for other Islamic educational institutions in developing leadership and digital innovation that balance moral, spiritual, and technological aspects.